Hydrophilic and underwater super-oleophobic modified fabric material as well as preparation method and application thereof
By sulfonating formic acid lignin and synergistically constructing a hydration interface coating with cationic polymers, the problems of insufficient stability and anti-fouling ability of existing fabrics are solved, and the high hydrophilicity and underwater superoleophobic properties are improved, making it adaptable to extreme environments and in line with the requirements of green development.
Patent Information
- Application Number
- CN202511288455.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-10
- Publication Date
- 2025-11-11
AI Technical Summary
Existing oil-water separation functional fabrics are insufficient in terms of stability, low oil adhesion, and anti-fouling ability, and traditional methods have problems with environmental risks and insufficient chemical stability.
Using formic acid lignin as raw material, sulfonation modification is used to introduce sulfonic acid groups to form a natural polyelectrolyte material with high anion grafting density. This material is then synergistically combined with cationic polymers to construct a stable hydration interface coating, thereby improving hydrophilicity and underwater superoleophobic properties.
It improves the underwater oleophobic properties and stability of the fabric, has excellent rolling properties and self-cleaning ability, adapts to extreme environments, and meets the requirements of green and sustainable development.
Smart Images

Figure CN120925302A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fabric preparation technology, and in particular to a modified fabric material with hydrophilicity and underwater superoleophobicity, its preparation method, and its application. Background Technology
[0002] The high-intensity operation of petrochemical and marine transportation activities has made oily wastewater and sudden leaks a persistent threat to aquatic ecological security. While traditional polyvinylidene fluoride (PVDF) or fluorinated silica porous membranes can achieve oil-water separation, their preparation is energy-intensive, degradation is difficult, and the risk of microplastics is significant, contradicting the goal of carbon neutrality. In recent years, the materials science community has proposed a "hydrophilic / underwater superoleophobic" interface control strategy. By creating low surface energy structures and stable hydration layers in the aqueous phase, oil droplets exhibit contact angles >150°, opening up a new path for room-temperature, low-pressure, and sustainable oil-water separation.
[0003] The fibrous fabric combines millimeter-level interconnected channels with micrometer-level gaps, naturally forming a "macro-micro-nano" flux gradient; its flexible and rollable properties also make it easy to integrate with tubular, plate-type, and rotary separation components. The only drawback is insufficient surface energy and chemical activity, which requires functional coatings to impart synergistic wetting / anti-fouling capabilities.
[0004] Lignin, as the most abundant renewable aromatic polymer on Earth, is rich in functional groups such as hydroxyl and methoxy groups, providing multiple reaction sites for subsequent chemical modification. Among them, formic acid lignin obtained from pulping byproducts of formic acid pretreatment retains a high number of phenolic hydroxyl groups, has few impurities, and a narrow molecular weight distribution, making it an ideal precursor for biomass modification.
[0005] Recently, zwitterionic polymers and anionic / cationic polyelectrolytes with high charge grafting density have been found to be very effective in treating viscous oils because the cationic and anionic head groups have excellent water affinity and can form a robust and stable hydration layer.
[0006] Existing oil-water separation functional fabrics generally rely on fluorinated compounds or a single hydrophilic coating system. Although they can exhibit high underwater superoleophobicity in the short term, their surface hydration layer has poor stability and is prone to failure when exposed to viscous oils or complex aquatic environments for extended periods. Furthermore, fluorinated components pose risks of environmental residue and bioaccumulation, failing to meet the requirements of green and sustainable development. Traditional natural polymer modification methods often rely on hydrophilic components with insufficient chemical stability or low charge density, resulting in fabrics that are inadequate in terms of durability, low oil adhesion, and stain resistance. Summary of the Invention
[0007] In view of this, to address the technical problems of poor stability and insufficient performance in durability, low oil adhesion, and anti-fouling ability of existing oil-water separation functional fabrics, this invention provides a hydrophilic and underwater superoleophobic modified fabric material, its preparation method, and its application in improving the oleophobic properties of fabrics. Following the development trend of green, fluorine-free materials, formic acid lignin is used as a raw material. Through sulfonation modification, sulfonic acid groups are introduced into its molecular structure, transforming it from a neutral polymer into a natural polyelectrolyte material with a high anion grafting density. This material can form a stable hydration layer in water. Furthermore, by synergistically constructing a sustainable, fluorine-free, and stable hydration interface coating with cationic polymers, the material's ability to regulate the aqueous phase interface and its underwater oleophobic properties are significantly improved, achieving an organic unity of high hydrophilicity, high stability, and excellent underwater superoleophobic properties. This improves underwater oleophobic performance while also possessing excellent rollability and maintaining good stability in extreme environments.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] In a first aspect, the present invention provides a method for preparing a hydrophilic and underwater superoleophobic modified fabric material, comprising the following steps:
[0010] Step (1): Highly active formic acid lignin was extracted from lignocellulose raw materials using a small molecule phenol-short chain polyol-organic acid synergistic cooking method;
[0011] Step (2): Sulfonate the highly active formic acid lignin obtained in step (1) to obtain sulfonated formic acid lignin;
[0012] Step (3): Mix the sulfonated formic acid lignin obtained in step (2) with the cationic polymer to obtain a mixed solution;
[0013] Step (4): Immerse the fabric in the mixed solution of step (3), remove and dry to obtain the modified fabric material.
[0014] Preferably, in step (2), a cooking liquid composed of a mixture of activating reagent and sulfonating reagent is used to sulfonate and modify the highly active formic acid lignin in step (1).
[0015] Preferably, the sulfonating agent and the highly active formic acid lignin are in a mass ratio of 1-10:10-20, more preferably 2.5-5:10;
[0016] The activating agent and the highly active formic acid lignin are in a mass ratio of 1-10:10-20, preferably 2.5-5:10.
[0017] Preferably, in step (3), the cationic polymer is a polymeric compound containing primary amine, secondary amine, tertiary amine or quaternary ammonium salt groups, and the number average molecular weight is preferably greater than 1000 Da.
[0018] Preferably, the cationic polymer is selected from at least one of polydiallyldimethylammonium chloride, branched polyethyleneimine, linear polyethyleneimine, polypropyleneimine, polyquaternary ammonium salt polymers, cationic chitosan derivatives and their salts, copolymers or mixtures.
[0019] Preferably, in step (3), the mass ratio of sulfonated formic acid lignin to cationic polymer is 1-5:1-10, more preferably 1:1-2.
[0020] Preferably, in step (3), the volume fraction of the cationic polymer is 40%.
[0021] Secondly, the present invention provides a modified fabric material with hydrophilicity and underwater superoleophobicity, characterized in that it is prepared by the above-mentioned preparation method of the modified fabric material with hydrophilicity and underwater superoleophobicity.
[0022] Preferably, the raw materials comprise the following parts by weight:
[0023] Sulfonated formic acid lignin 20-65 parts; cationic polymer 5-35 parts; sulfonating agent 3-25 parts; activating agent 3-25 parts; fabric 10-50 parts.
[0024] Thirdly, the present invention provides the application of the above-mentioned hydrophilic and underwater superoleophobic modified fabric materials in improving the oleophobic properties of fabrics.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) This invention takes highly active formic acid lignin from renewable biomass as the core, and achieves hydrophilicity and functionalization of the interface through sulfonation-zwitterion synergistic construction. It is fluorine-free throughout the entire process, avoiding the environmental and health risks of fluorides, and has high stability and excellent oil-water separation performance, which is in line with the trend of green and sustainable development.
[0027] (2) A large number of sulfonic acid groups are introduced through sulfonation reaction assisted by activator to construct an anionic polyelectrolyte skeleton, and crosslinked with cationic polymers through electrostatic interaction and hydrogen bonding to construct a three-dimensional coating structure with high bonding strength and excellent interface stability.
[0028] (3) The lignin-based composite coating material prepared by the present invention is applied to the fabric surface after the lignin-based self-composite coating is attached, which can greatly increase the fabric contact angle and effectively improve the underwater oleophobic properties of the fabric. At the same time, the lignin composite coating prepared by the present invention has good stability and excellent self-cleaning ability, and can adapt well to harsh environments.
[0029] (4) This invention constructs a natural anionic polyelectrolyte by sulfonating formic acid lignin, which forms a stable hydration layer and a low oil adhesion interface on the fabric surface, thereby achieving efficient and sustainable underwater superoleophobic function within the framework of green materials, which has important scientific value and application significance.
[0030] Other advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0031] Figure 1 The images show the surface of the sulfonated formic acid lignin-based modified fabric with the best underwater oleophobic properties obtained under different gradients in Example 1. From left to right, 1-5 are samples 4, 10, 15, 22 and 29 in Example 1.
[0032] Figure 2 These are test images of the underwater rolling properties of industrial sodium lignin sulfonate, sulfonated formic acid lignin, and sulfonated formic acid lignin-based modified fabrics fixed on glass slides. From top to bottom, A, B, and C represent industrial sodium lignin sulfonate, sulfonated formic acid lignin, and sulfonated formic acid lignin-based modified fabrics, respectively. From left to right, these are test images of different lignin loads at 0s, 1s, and 2s. Detailed Implementation
[0033] This invention provides a method for preparing a hydrophilic and underwater superoleophobic modified fabric material, comprising the following steps:
[0034] Step (1): Highly active formic acid lignin is extracted from lignocellulose raw materials using a small molecule phenol-short chain polyol-organic acid synergistic cooking method. This process effectively inhibits the intermolecular condensation reaction of lignin, retains a high proportion of β-O-4 structure, and significantly enriches active sites such as phenolic hydroxyl groups. Compared with ordinary industrial lignin (such as sodium lignin sulfonate), it has a lower degree of condensation and a higher density of active groups, enabling higher sulfonic acid grafting efficiency and more uniform distribution during sulfonation.
[0035] The small-molecule phenol-short-chain polyol-organic acid synergistic cooking method is a technique for extracting highly active formic acid lignin from lignocellulose raw materials. This method combines small-molecule phenols, short-chain polyols, and organic acids to form a synergistic reaction system, effectively depolymerizing lignin and improving its extraction efficiency and activity. Small-molecule phenols are small-molecule compounds with phenolic hydroxyl (-OH) structures, typically possessing strong antioxidant and reactivity properties, and can promote lignin depolymerization or extraction. Short-chain polyols are organic compounds containing multiple hydroxyl (-OH) groups with short carbon chains (such as ethylene glycol and glycerol). They are often used as solvents or auxiliaries in chemical reactions to improve the stability and efficiency of the reaction system. Organic acids are organic compounds containing carboxyl groups (-COOH), such as formic acid, acetic acid, and lactic acid. In lignocellulose treatment, organic acids can act as catalysts, helping to decompose the complex structure between lignin and cellulose.
[0036] Step (2): The highly active formic acid lignin obtained in step (1) is sulfonated to obtain an aqueous solution of sulfonated formic acid lignin. After separation and purification, the target product is obtained by freeze-drying and then ground to obtain sulfonated formic acid lignin powder. For example, the highly active formic acid lignin is precisely sulfonated using a cooking solution composed of a certain ratio of activating reagent and sulfonating reagent. The mass ratio of sulfonating reagent to highly active formic acid lignin is 1-15:10-20, preferably 1-5:10; the mass ratio of activating reagent to highly active formic acid lignin is 1-10:10-20, preferably 1-5:10.
[0037] Sulfonation modification preferably uses sulfite compounds as sulfonating agents and introduces activators to enhance the molecular chain reaction activity, thereby obtaining anionic polyelectrolyte-type sulfonated lignin with high charge density and uniform distribution. This product, while retaining the aromatic backbone and polyphenolic hydroxyl groups, significantly improves hydrophilicity and chemical stability, providing a solid molecular basis for subsequent crosslinking with cationic polymers.
[0038] The sulfonating agent can be a conventional sulfite / bisulfite system found in the prior art, and used within its conventional concentration range. Therefore, in some embodiments, the sulfonating agent is selected from at least one of sodium sulfite, sodium bisulfite, potassium sulfite, and potassium bisulfite, and can be supplemented with sulfur-containing additives (such as thiosulfate, sulfur dioxide) and water / alcohol mixed solvents (such as methanol, ethanol) as needed to improve solubility and mass transfer performance.
[0039] The activating agent can be a solvent used in conventional activation methods in the prior art, and can be used within its conventional concentration range. Therefore, in some embodiments, the activating agent is selected from at least one of potassium hydroxide, sodium hydroxide, alkali metal carbonates, or combinations thereof.
[0040] Specifically, the preparation method of sulfonated formic acid lignin can be as follows:
[0041] Formic acid lignin, sulfonating agent, and / or activating agent are added to a high-temperature reactor in a specified ratio. Deionized water is added and the mixture is stirred until homogeneous. The reactor is then heated at high temperature and centrifuged to obtain sulfonated formic acid lignin. The preferred heating temperature is 60–200°C, more preferably 100–180°C, and most preferably 100–140°C. The preferred heating rate is 5–10°C / min, and the preferred heating time is 10–900 min, more preferably 10–180 min, and most preferably 30–60 min. The preferred material-to-liquid mass ratio for centrifugation is 1:4–1:20, more preferably 1:7–1:10. The preferred centrifugation speed is 1000–8000 rpm, more preferably 1000–2000 rpm, and the preferred centrifugation time is 5–30 min, more preferably 5–10 min.
[0042] Step (3): The sulfonated formic acid lignin obtained in step (2) is mixed evenly with the cationic polymer to obtain a mixed solution. The mixing conditions for the sulfonated formic acid lignin and the cationic polymer are: a material-to-liquid mass ratio of 1:10 to 1:200, preferably 1:20 to 80, and more preferably 1:40 to 1:70. The mass ratio of sulfonated formic acid lignin to the cationic polymer is 1 to 5:1 to 10, preferably 1:1 to 2. The volume fraction of the cationic polymer is 40%.
[0043] The cationic polymer is a high molecular weight compound containing primary, secondary, tertiary amine, or quaternary ammonium salt groups, preferably with a number average molecular weight greater than 1000 Da, to ensure the formation of a continuous and stable polymer network layer on the fabric surface. The cationic polymer is selected from at least one of polydiallyldimethylammonium chloride, branched polyethyleneimine, linear polyethyleneimine, polypropyleneimine, polyquaternary ammonium salt polymers, cationic chitosan derivatives and their salts, copolymers, or mixtures. The above compounds can be used alone or in combination of two or more to achieve performance regulation.
[0044] Step (4): Immerse the fabric in the mixed solution of step (3), turning it over once every 3 hours after a period of time (e.g., after immersion for 6 hours, turn it over once every 3 hours) to ensure uniform deposition. After drying, the modified fabric material is obtained. The immersion temperature is preferably 25-50℃, more preferably 25-40℃, and the immersion time is preferably 3-24 hours, more preferably 3-6 hours. The drying temperature is preferably 50-120℃, more preferably 50-60℃, and the drying time is preferably 0.5-4 hours, more preferably 2-3 hours.
[0045] The fabric is preferably a cotton fabric, and more preferably a cotton-polyester blended fabric. The fabric is preferably pretreated, specifically by ultrasonically cleaning it alternately with ethanol and deionized water, and then drying it for later use.
[0046] The hydrophilic and underwater superoleophobic modified fabric material prepared by the above preparation method of the present invention comprises the following parts by weight of raw materials:
[0047] Sulfonated formic acid lignin 20-65 parts; cationic polymer 5-35 parts; sulfonating agent 3-25 parts; activating agent 3-25 parts; fabric 10-50 parts.
[0048] The technical solution of the present invention will be clearly and thoroughly described below with reference to specific embodiments. It should be noted that the specific embodiments are explanations of the present invention rather than limitations.
[0049] Experimental methods in the following examples that do not specify specific conditions should be performed according to conventional methods and conditions, or according to the product instructions. Furthermore, all reagents and raw materials used in this invention are commercially available.
[0050] Example 1
[0051] (1) The preparation method of sulfonated modified formic acid lignin specifically includes the following steps:
[0052] Raw material: Highly active formic acid lignin.
[0053] Cooking vessel: Hastelloy reactor, heated by a programmable temperature-controlled heating mantle.
[0054] Step 1. The above-mentioned amount of blended cooking liquid (sulfonating reagent + activating reagent) and highly active formic acid lignin are loaded into a reaction vessel, heated to 140°C and cooked for 1 hour. The heating rate during the heating process is 5.0°C / min.
[0055] Step 2. After the cooking is complete, cool the reactor to room temperature and remove the black liquor.
[0056] Step 3. Centrifuge the black liquor at 5000 rpm for 5 min.
[0057] Step 4. Remove the supernatant and freeze-dry it, then grind it into powder.
[0058] (2) A method for preparing sulfonated formic acid lignin-based modified fabrics, comprising the following steps:
[0059] Step 1: Mix sulfonated formic acid lignin and cationic polymer, then add deionized water so that the volume fraction of cationic polymer in the solution after adding deionized water is 40%, and then stir magnetically for 10 minutes.
[0060] Step 2: The fabric is ultrasonically treated with anhydrous ethanol and deionized water alternately. The treated fabric is then immersed in the above-prepared solution for 6 hours. The cotton fabric is turned over every 3 hours to ensure uniform deposition.
[0061] Step 3: Remove the cotton fabric from Step 2 after impregnation, wash it, and dry it at 50℃ for 2 hours to obtain the modified fabric. The types and amounts of components in the raw material composition are shown in Tables 1 and 2.
[0062] Table 1. Proportions of materials for cooking
[0063]
[0064]
[0065] Table 2
[0066]
[0067]
[0068] Table 3. Underwater contact angles of sulfonated formic acid lignin-based modified fabrics
[0069]
[0070]
[0071] The comparison of samples 1-6 shows that when the sodium sulfite content is 10%, the oleophobic angle of the modified fabric gradually increases as the amount of NaOH used increases, with sample 4 showing the best effect.
[0072] The comparison of samples 7 to 12 shows that when the sodium sulfite content is 20%, the oleophobic angle of the modified fabric gradually increases as the amount of NaOH increases, with sample 10 showing the best effect.
[0073] The comparison of samples 13-18 shows that when the sodium sulfite content is 30%, the oleophobic angle of the modified fabric gradually increases as the amount of NaOH increases, with sample 15 showing the best effect.
[0074] The comparison of samples 19-24 shows that when the sodium sulfite content is 40%, the oleophobic angle of the modified fabric gradually increases as the amount of NaOH increases, with sample 22 showing the best effect.
[0075] The comparison of samples 25-30 shows that when the sodium sulfite content is 50%, the oleophobic angle of the modified fabric gradually increases as the amount of NaOH increases, with sample 29 showing the best effect.
[0076] A comparison of samples 4, 10, 15, 22 and 29 shows that increasing the sodium sulfite concentration significantly enhances the sulfonation effect and increases the contact angle.
[0077] As shown in the table above, with a fixed Na2SO3 mass ratio of 50%, the modified fabric exhibits good underwater oleophobic properties, with a maximum contact angle of 154°, and droplets can remain in the water for a certain period of time, resulting in a significant increase in the dynamic contact angle. The modified fabric shows the best oleophobic effect when the NaOH mass ratio is 40%.
[0078] Example 2
[0079] Sample 29 from Example 1, prepared with sulfonated formic acid lignin: Na2SO3: NaOH in a ratio of 10:5:4, was used to conduct experiments on the sulfonated formic acid lignin-based modified fabric. The three groups of fabrics loaded with sulfonated formic acid lignin-based modified fabrics were immersed in HCl solution (pH=2), NaOH solution (pH=12), and NaCl solution (pH=7) for 24 hours, respectively. The underwater oil contact angle (OCA) of the modified fabric was tested using an optical contact angle meter (OCA50). 8 μL of water was dripped onto the surface of the test sample using a syringe, and the droplet was photographed and its corresponding contact angle was measured. The average value of five tests was used.
[0080] The test results are shown in Table 4.
[0081] Table 4. Contact Angle Test Results of Harsh Environmental Adaptability Experiment
[0082] Environmental conditions Contact angle (°) Oil droplet residence time (min) HCl solution (pH=2) 138.4 >5 NaCl solution (pH=7) 142.1 >5 NaOH solution (pH=12) 151.6 >5
[0083] As shown in Table 4 above, cotton fabrics coated with lignin-based self-cleaning coatings maintained high initial contact angles (above 135°) after immersion in HCl solution (pH=2), NaCl solution (pH=7), and NaOH solution (pH=12) for 24 hours, with water droplet residence time exceeding 5 minutes. Therefore, the lignin-based composite coating can effectively adapt to harsh environments.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0085] Oleophobicity test
[0086] The sulfonated formic acid lignin-based modified fabric (sample 29) prepared in Example 1 (2) was tested. The underwater oil contact angle (OCA) was tested using an optical contact angle meter (OCA50). 8 μL of water was dropped onto the surface of the test sample by controlling the syringe. The droplets were photographed and their corresponding contact angles were measured. The average value of five tests was taken as the test result.
[0087] Figure 1 The images shown are of the oleophobic surface of the sulfonated formic acid lignin-based modified fabric prepared in Example 1. The optimal samples from each gradient were selected for comparison. After loading with the lignin-based composite coating material prepared in this embodiment of the invention, the contact angle increased significantly. The contact angle of the sulfonated formic acid lignin-based modified fabric prepared in Sample 29 of Example 1 reached 154°, and the water droplet residence time was greater than 5 minutes. Therefore, the sulfonated formic acid lignin-based modified fabric prepared in this invention has good stability and can be used to improve the oleophobicity of the substrate, with Sample 29 showing the best effect.
[0088] Underwater rolling and self-cleaning test
[0089] Take the sulfonated formic acid lignin-based modified fabric prepared from sample 29 in Example 1, fix the sulfonated formic acid lignin-based modified fabric onto an inclined glass slide, and place it in water, keeping the surface flat. Use a needle to drop oil-red dyed dichloromethane onto the surface of the cotton fabric and observe whether the oil droplet rolls off naturally. The results are as follows. Figure 2 As shown.
[0090] like Figure 2 As shown, the sulfonated formic acid lignin-based modified fabric exhibits excellent self-cleaning ability: after a few drops of oil are applied using a dropper, no rolling marks are observed on the industrial sodium lignin sulfonate (Figure A), while there is brief rolling on the sulfonated formic acid lignin (Figure B). However, the sulfonated formic acid lignin-based modified fabric (Figure C) demonstrates excellent rolling performance, with no oil remaining on the fabric, leaving the fabric surface clean as before. Therefore, the sulfonated formic acid lignin-based modified fabric possesses excellent rolling properties.
[0091] The above description is merely a preferred embodiment of the present invention. However, the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified fabric material with hydrophilic and underwater superoleophobic properties, characterized in that, Includes the following steps: Step (1): Highly active formic acid lignin was extracted from lignocellulose raw materials using a small molecule phenol-short chain polyol-organic acid co-cooking method; Step (2): The highly active formic acid lignin obtained in step (1) is subjected to sulfurous acid sulfonation reaction to obtain sulfonated formic acid lignin; Step (3): Mix the sulfonated formic acid lignin obtained in step (2) with the cationic polymer to obtain a mixed solution; Step (4): Immerse the fabric in the mixed solution of step (3), remove and dry to obtain the modified fabric material.
2. The method for preparing a hydrophilic and underwater superoleophobic modified fabric material according to claim 1, characterized in that, In step (2), the highly active formic acid lignin in step (1) is modified by sulfonation using a cooking liquid composed of a blend of activating reagent and sulfonating reagent.
3. The method for preparing a hydrophilic and underwater superoleophobic modified fabric material according to claim 2, characterized in that, The sulfonating agent and the highly active formic acid lignin are in a mass ratio of 1-15:10-20, preferably 2.5-5:10; The activating agent and the highly active formic acid lignin are in a mass ratio of 1-10:10-20, preferably 2.5-5:
10.
4. The method for preparing a hydrophilic and underwater superoleophobic modified fabric material according to claim 1, characterized in that, In step (3), the cationic polymer is a high molecular weight compound containing primary amine, secondary amine, tertiary amine or quaternary ammonium salt groups, and the number average molecular weight is preferably greater than 1000 Da.
5. The method for preparing a hydrophilic and underwater superoleophobic modified fabric material according to claim 4, characterized in that, The cationic polymer is selected from at least one of polydiallyldimethylammonium chloride, branched polyethyleneimine, linear polyethyleneimine, polypropyleneimine, polyquaternary ammonium salt polymers, cationic chitosan derivatives and their salts, copolymers or mixtures.
6. The method for preparing a hydrophilic and underwater superoleophobic modified fabric material according to claim 1, characterized in that, In step (3), the mass ratio of sulfonated formic acid lignin to cationic polymer is 1-5:1-10, preferably 1:1-2.
7. A method for preparing a hydrophilic and underwater superoleophobic modified fabric material according to any one of claims 1-6, characterized in that, In step (3), the volume fraction of the cationic polymer is 40%.
8. A modified fabric material with hydrophilic and underwater superoleophobic properties, characterized in that, It is prepared by any one of the preparation methods of the hydrophilic and underwater superoleophobic modified fabric material according to any one of claims 1-7.
9. A modified fabric material with hydrophilic and underwater superoleophobic properties according to claim 8, characterized in that, Includes the following raw materials by weight: Sulfonated formic acid lignin 20-65 parts; cationic polymer 5-35 parts; sulfonating agent 3-25 parts; activating agent 3-25 parts; fabric 10-50 parts.
10. The application of the hydrophilic and underwater superoleophobic modified fabric material as described in claim 8 or 9 in improving the oleophobic properties of fabrics.